The RED-100 experiment. (1st November 2022) - Akimov, D.Yu.; Alexandrov, I.S.; Alyev, R.R.; Belov, V.A.; Bolozdynya, A.I.; Etenko, A.V.; Galavanov, A.V.; Glagovsky, E.M.; Gusakov, Y.V.; Khromov, A.V.; Kiselev, S.M.; Konovalov, A.M.; et al.
Abstract: The RED-100 two-phase xenon emission detector has been deployed at 19-m distance from the reactor core of the Kalinin Nuclear Power Plant (KNPP) in 2021–2022 for investigation of the possibility to observe reactor antineutrinos using the effect of coherent elastic neutrino-nucleus scattering (CE ν NS). The performance of the main systems of the RED-100 setup at operating nuclear power plant is described. There is no correlation of the radioactive background at the experimental setup site with ON and OFF states of the reactor. The data taking run was carried out at the beginning of the year 2022 and covered both the reactor OFF and ON periods.